A iniciação científica no ensino médio: contexto atual, desafios e perspectivas na área de ciências da natureza - Gonçalves, Daniela Antunes da Costa (2018)
At present, many questions emerge in society involving science, because the global problems, increasingly complex, end up encountering difficulties of discussion and understanding by most individuals, since there still prevail simplistic and naive visions of scientific development. It should be emphasized that this situation is related to the crisis faced in the area of science education, since most of the students finish basic education without acquiring the knowledge necessary for a full understanding of the socio-scientific issues present in today's society. The worrying educational and social situation highlights the need for reformulations in the different aspects that cover the field of education, for the realization of a pedagogical practice that allows the formation of a critical and reflexive subject on the problems that surround society and the production of science. In this scenario, many possibilities can be highlighted, in order to provide individuals with this ability to read the scientific and social world, one of them is education through research, with the practice of scientific initiation since the early years. Within this approach to research as the guiding thread of student protagonist, the relevance of the present research proposal emerged, since it has as central problem: "How is the Scientific Initiation being developed in High School in the area of Natural Sciences? ". In this way, the work sought to analyze the development of the Scientific Initiation, in the area of Natural Sciences, in the High School of the State Education Network of the city of Alegrete. Therefore, an in-depth study of the reality lived in the city of Alegrete was done through a qualitativeexploratory approach, using documentary analysis of the pedagogical political projects of the schools, applying interviews with teachers in the area of science nature that act in the high school, and analysis of a proposal of Scientific Initiation in the High School of a school of the private network. From the data collection, they were analyzed based on the discursive textual analysis. The findings of the research showed that the educators of the state network develop practices directed to Scientific Initiation within their disciplines, according to the documents guiding pedagogical actions (PPPs), however they face difficulties in structuring a more in-depth view of scientific research in space school. From the analysis of the pedagogical proposal, it was possible to point out that the research institution presents the Scientific Initiation as the structuring axis of its pedagogical conceptions, bringing to the everyday in a structured way the teaching by the research, through an institutional project, with the denomination of Mostra de Scientific research. The pedagogical experience analyzed in this research path serves as a reference for the needs pointed out in the public network of education, since the educators expressed the desire of the development of the Scientific Initiation; however, they lack adequate support and training in the education system. It is a great challenge to shift research to the center of the teaching-learning process, but it is pertinent to look for initial actions in this direction